Pengaruh Pemberian Fraksi Etil Asetat Daun Kelor (Moringa Oleifera Lamk.) terhadap Daya Ingat Mencit Jantan dengan Menggunakan Metode Labirin Y-Maze - Bagas Ardiyantoro; Muhamad Farid Nurohman Krisnadi; Danang Raharjo (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Memory decline is an early symptom of neurodegenerative disorders such as dementia, often caused by oxidative stress due to an imbalance between the production of Reactive Oxygen Species (ROS) and the body’s antioxidant defense system. Moringa leaves (Moringa oleifera Lamk.) are known to contain flavonoids, particularly quercetin, which exhibit antioxidant activity and are potentially beneficial for cognitive function. This study aimed to evaluate the effect of the ethyl acetate fraction of Moringa leaves on memory improvement in male mice induced with 10% ethanol. The ethyl acetate fraction was obtained through maceration using 70% ethanol, followed by fractionation with ethyl acetate. A total of 25 male mice were divided into five groups: negative control (1% CMC Na), positive control (Ginkgo biloba 60 mg/kgBW), and three treatment groups receiving the ethyl acetate fraction of Moringa leaves at doses of 50, 100, and 150 mg/kgBW. Memory performance was assessed using the Y-Maze method, consisting of three phases: acclimatization (T0), induction (T1), and treatment (T2). Data were analyzed using one-way ANOVA followed by Duncan’s post hoc test.The results showed that the ethyl acetate fraction of Moringa leaves significantly (p value < 0.05) reduced error counts and latency time, with the most optimal effect observed at a dose of 150 mg/kgBW. This dose led to a significant improvement in memory performance compared to the control groups, including the positive control. These findings suggest that the ethyl acetate fraction of Moringa leaves has a more effective potential to enhance memory compared to the positive control, with a time difference of 40 seconds and an error rate difference of 11.67%.